Consumer energy management system with integration of smart meters - Pereira, R. (2017)
Abstract This paper develops an energy management system with integration of smart meters for electricity consumers in a smart grid context. The integration of two types of smart meters (SM) are developed: (i) consumer owned \{SM\} and (ii) distributor owned SM. The consumer owned \{SM\} runs over a wireless platform–ZigBee protocol and the distributor owned \{SM\} uses the wired environment–ModBus protocol. The \{SM\} are connected to a \{SCADA\} system (Supervisory Control And Data Acquisition) that supervises a network of Programmable Logic Controllers (PLC). The \{SCADA\} system/PLC network integrates different types of information coming from several technologies present in modern buildings. The developed control strategy implements a hierarchical cascade controller where inner loops are performed by local PLCs, and the outer loop is managed by a centralized \{SCADA\} system, which interacts with the entire local \{PLC\} network. In order to implement advanced controllers, a communication channel was developed to allow the communication between the \{SCADA\} system and the \{MATLAB\} software.